Traffic grooming in static wavelength division multiplexing networks. - Cerutti, Isabela (IEEE Communications magazine)
Advances in wavelength-division multiplexing technology have made it possible to design point-to-point transmission systems with unprecedented per-wavelength high capacity. This capacity may be exploited to design optical networks, in which end nodes are interconnected by circuits consisting of wavelengths. Contrary to early expectations, however, most of today's end-to-end applications require only sub-wavelength bandwidth. This bandwidth mismatch makes wavelength circuits inefficient in many cases, unless multiple traffic flows are time multiplexed together on the same wavelength. This practice is often referred to as traffic grooming. In this survey the authors address the issue of achieving efficient traffic grooming in static WDM networks. A great deal of discussion is devoted to the problem of determining which network solution is the most cost effective, taking into account the network topology, volume of traffic, possible optical impairments at high transmission rates, and cost ratio between electronic and optical components.